Adoption of Learning Management Systems in Higher Education: A Qualitative Analysis of Enabling Factors (International Journal of Scientific Research and Management (IJSRM), 2024)
The widespread and affordability of multimedia devices such as computers, smartphones and iPads among others has now facilitated teaching and learning to take place in formal as well as informal settings. The teaching and learning process can now be encaged at any time from any part of the globe and open to all through the use of hardware and software, converging teacher and students in an online platform. This study has as objective to examine factors that amplify the adoption of Learning Management Systems, especially after the outbreak of COVID -19 which called for social distancing that left many schools on the global platform in a state of pandemonium. The sudden shutdown of schools and the need to ensure continuity in schooling left no option for institutions at all levels to adopt the new technology of learning online. The changing trends in education have enabled the development of ubiquitous Learning Management System (LMS) to resolve the challenge of continuous schooling in the face of crisis. LMS is a virtual environment designed to connect teachers and students in an online platform. This study which used qualitative descriptive method with an emphasis on thematic content analysis seeks to investigate enabling factors for the integration of LMS in the 21st century classroom. Informants consisted of 8 teachers drawn from two private universities. The findings of the study revealed that critical factors, classified as technology factors, social influence factors and human factors will influence the integration of LMS in the school. This paper therefore provides insight of enabling factors and hence learning effectiveness.